ANALISIS KUALITAS WEBSITE PENDAFTARAN CAMARU UPNVJ JALUR SELEKSI MANDIRI MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Annisa Shabirah, (2023)
The UPNVJ CAMARU Registration Website is an information system used as a means of disseminating information related to the stages and registration of new students of the Jakarta Veteran National Development University who enter through the UPNVJ independent selection route. The importance of the existence of this website as a system that aims to facilitate the registration process and also the dissemination of information requires this website to be able to present accurate and quality information. Therefore, it is necessary to evaluate the CAMARU Registration website to find out problems and improve website quality. The purpose of this study is to analyze the quality of the CAMARU Registration website and determine the indicators that are the focus of attention to be improved. The results of this study found that the average webqual index value was 0.74 which means that the level of service quality on the UPNVJ CAMARU Registration website is considered good according to users. However, the results of GAP analysis on the dimensions of Service interaction quality and Usability are still negative and quite high, namely -0.48 and 0.39. Then, there are 6 attributes in quadrant I based on importance performance analysis which are considered important and become a priority for improvement